Assessment of Water Quality of Neota Dam for Determining its Pollution Status - Nidhi Singh; Swati Gupta (The Bioscan, 2025)
The current study is to track and evaluate the level of physic-chemical and heavy metal contamination in a water reservoir of Jaipur region and the health hazards due to bioaccumulation. Triplets from specific places inside the Water body were used to collect water samples constantly over a 12-month period, from December 2022 to November 2023 in a quarterly basis. Strict adherence to IS and APHA standards was maintained throughout the sampling and testing process. The observed physico-chemical parameters and heavy metal concentrations were then contrasted with the permissible limits as per the guidelines of the National Plan for Conservation of Aquatic Ecosystem (NPCA), which is overseen by the Ministry of Environment, Forests, and Climate Change of the Indian government. The levels of heavy metal in water and fishes were analysed using Atomic Absorption Spectrophotometer from the collected samples.